Gastric remnant cancer: a comprehensive narrative review from carcinogenesis to treatment - Portillo-Miño, José Darío (2025)
Gastric remnant cancer is cancer secondary to partial gastrectomy after five years. Peculiarities due to the gastrectomy status may influence this type of GC. Modifications in the gastric microbiome, luminal pH, dietary habits, increased bile reflux, and Epstein-Barr virus infection, together with the traditional GC risk factors, cooperate to increase the risk of cancer in the remnant stomach. H. pylori infection has been widely associated with GC, and its role in the pathogenesis of the remnant stomach, as well as the preventive effect of its eradication after gastrectomy, are issues of great scientific interest. Bariatric surgery is another condition potentially related to increased GC risk and challenges to its diagnosis. In this scenario, this article aims to review the current evidence of the fundamental aspects involved in developing the gastric remnant cancer